Beyond Attitudes: Spiritual Intelligence and Rationalization as Predictors of Academic Dishonesty - Dogi, Dean Charlos Padji; Mangoting, Yenni; Hokil, Caroline (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2025)
This study investigates the influence of spiritual intelligence, attitude, and rationalization on students’ intention to engage in academic dishonesty by integrating the Theory of Planned Behavior (TPB) and Fraud Triangle Theory (FTT). Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on survey data collected from undergraduate students, the study tests five hypotheses involving direct effects between the constructs. The findings indicate that spiritual intelligence significantly increases ethical attitudes and reduces rationalization. However, neither spiritual intelligence nor attitude has a significant direct effect on students’ intention to cheat. Instead, rationalization emerges as the strongest predictor of intention, highlighting its central role in enabling unethical behavior through cognitive justification. The results support theoretical calls to incorporate moral and spiritual variables into behavioral models while also emphasizing rationalization as a critical explanatory mechanism. Practical implications suggest that higher education institutions should integrate value-based education, directly challenge rationalizing beliefs, and strengthen institutional integrity culture. Limitations include the study’s cross-sectional nature and reliance on self-reported measures. Future research should explore mediating effects and extend the model using longitudinal or experimental approaches. This study contributes to academic ethics literature by offering an enriched understanding of psychological and spiritual factors behind student cheating behavior. These findings offer valuable insights for business pedagogy by highlighting how moral and cognitive factors in academic settings may shape future ethical behavior in organizational contexts.